Analisis Hukum Pidana Islam Dan Hukum Positif Terhadap Penganiayaan Yang Dilakukan Oleh Orang Abnormal Di Nagari Panyakalan Kecamatan Kubung Kabupaten Solok - Redo Febrian (Yayasan Lembaga Studi Makwa, 2022)
The background of this research is because in the midst of society there are often cases of abuse committed by abnormal people. One of them is the case that occurred in Nagari Panyakalan, Kubung District. This study aims to find out how the of of abuse perpetrated by abnormal people in Nagari Panyakalan, as well as the views of Islamic law and positive law on the settlement of cases of abuse perpetrated by these abnormal people. This research uses field research so that the main source of data is primary data, namely the results of interviews conducted with the community related to this research. Based on the results of the research, it can be that the of of abuse committed by abnormal people in Nagari Panyakalan was taken through an agreement by making peace, efforts to make peace were carried out through meetings attended by each heir's mamak head from both parties. In Islamic law, the sanction for persecution is qishash, if the victim's family pardons it, it is replaced with diyat. This applies to the perpetrators who are legally capable, if the perpetrators are not legally competent or abnormal then this sanction cannot be carried out. Whereas in positive law, perpetrators of criminal acts who experience mental disorders have been regulated in Article 44 paragraph (1) of the Criminal Code, that is, anyone who commits an act for which he cannot be held liable because his soul is disabled in development or disturbed due to illness, is not punished.